Research discourses on entrepreneurship and social entrepreneurship in digital media: a critical analysis - Casaqui, Vander (2017)
A recent phenomenon arouses our attention: the profusion of reports, studies and surveys about the entrepreneurial scene. Such materials become popular through free access in digital media, taking part in communication strategies of several corporations. In this scenario, we propose a critical analysis of recent research reports that develop scenarios on entrepreneurship and social entrepreneurship, in Brazil and worldwide. The guiding questions of this work are: What projects of society emerge from the studied researches? What are the social roles assigned to entrepreneurs and social entrepreneurs in the diagnosis of the present and future projections? The theoretical framework include authors such as Ehrenberg, Boltanski & Chiapello, Weber and Foucault.